Transaction cost and informality in the sending of remittances: proposal of a model - González Gutiérrez , José Javier (Posgrados de la División de Ciencias Económica Administrativas, 2023)
With a registered amount three times larger than the official development assistance, remittances have become an important source of income for families and countries in conditions of poverty alike. According to the literature, the volume of unregistered remittances that flow through informal channels can reach anywhere between 50 and 250 percent of registered remittances flowing through formal channels. In large part due to high transaction costs associated with the transfer of remittances. To-date, the bulk of efforts to study the relationship between transaction costs and informal remittances has focused on the factors that determine the migrant’s choice in his country of residency. The scarce efforts to incorporate the receiver’s decision making have found that transaction costs are a decisive factor in the choice of remittance channel, and that a competitive and well-developed financial market reduces the transaction costs associated with the transfer of remittances. The goal of this first part of this research is to propose a model that incorporates microeconomic variables as determinant factors of the transaction costs and the choice of remittance channel in order to detect areas of opportunity that facilitate and promote the use of formal channels.